"Feathers on Fire": A Study of the Interplay Between Passion and Vulnerability in Dance - Suvi Satama (The Art of Management and Organization, 2022)
The focus of this paper is on the concepts of passion and vulnerability, which each provide viewpoints to develop the theoretical notion of embodied agency. To support my argument I present observations from an ethnographic study of dance. The paper describes how the relationship between passion and vulnerability works as a means for expanding embodied agency between off and on-stage, and exposes the aspects through which the interrelation between these concepts materialize among professional dancers. The paper contributes to the surprisingly thin discussion of embodiment at work in organizational studies by deepening our understanding of the link between passion, vulnerability and embodied agency – a triangle deeply connected to all (embodied) professions.